2017
DOI: 10.1007/s10329-017-0626-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping site preferences in Sapajus cay Illiger 1815 (Primates: Cebidae) in a disturbed fragment of the Upper Paraná Atlantic Forest, Rancho Laguna Blanca, Eastern Paraguay

Abstract: Wild primates can spend up to half of their lives sleeping, during which time they are subjected to many of the same selective pressures that they face when awake. Choosing an appropriate sleeping site can thus have important fitness consequences. We examined the sleeping site preferences of wild hooded capuchins (Sapajus cay) in a small degraded fragment of the Upper Paraná Atlantic Forest at Rancho Laguna Blanca (RLB) in eastern Paraguay. Sleeping trees and sites were identified during 5 months of field obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
1
12
0
6
Order By: Relevance
“…Some primates select particular microhabitats as a response to thermal stress. For example, Sapajus cay in eastern Paraguay prefer larger trees with a wider crown, which is thought to be related to thermoregulation (Smith, Hayes, Smith, & Dickens, 2018). Additionally, sleeping sites are also selectively used by primates to avoid thermal stress (Ellison et al, 2019; Karanewsky & Wright, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some primates select particular microhabitats as a response to thermal stress. For example, Sapajus cay in eastern Paraguay prefer larger trees with a wider crown, which is thought to be related to thermoregulation (Smith, Hayes, Smith, & Dickens, 2018). Additionally, sleeping sites are also selectively used by primates to avoid thermal stress (Ellison et al, 2019; Karanewsky & Wright, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the study group often slept in mixed forests and avoided sleeping in conifer forests. This was because mixed conifer forests were found at lower altitudes and had higher microclimate temperatures compared to conifer forests, and their denser tree cover provides shelter from rain, snow, and wind (Cui, Quan, & Xiao, ; Furuichi, Takasaki, & Sprague, ; Smith et al, ; Zhao, 1988). Previous studies also revealed that R. roxellana , and R. bieti slept in clusters ranging from two to eight individuals (Li et al, 2010; Zhang et al, ; Zhang, Li, Watanabe, & Qi, ; Zhang, Li, Qi, Macintosh, & Watanabe, ), with the benefits of sleeping in a huddles reducing energy expenditure through heat conservation (Kosheleff & Anderson, ; Scantlebury, Bennett, Speakman, Pillay, & Schradin, ; Seiler, Holderied, & Schwitzer, ).…”
Section: Discussionmentioning
confidence: 99%
“…They often choose sites that are relatively enclosed (valleys or dense canopy forests) that insulate and reduce their exposure to extreme weather conditions in order to maintain core body temperature (Smith, Knogge, et al, ; José‐Domínguez, Asensio, García, Huynen, & Savini, ). Locations of sleeping sites can also be influenced by food resource factors, where the selection of sites close to important food sources or to the last feeding patch can minimize travel costs and increase foraging efficiency (Anderson, ; Fan & Jiang, ; Smith, Hayes, Smith, & Dickens, ; Ar & Ml, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ambos patrones, tanto el patrón cambiante como el patrón de uso repetido de los sitios dormideros son interpretados como una estrategia que reduce el riesgo de depredación. La selección de estructuras de los árboles dormideros que permiten el agrupamiento de varios individuos durante la noche que fue descripta en este trabajo para los aulladores negros y dorados también ha sido reportada para Cebus apella (Zhang 1995) y Sapajus cay (Smith et al 2017). Además, hemos encontrado sustento para la función social que cumplen los árboles dormideros representando sitios de reunión que facilitan las interacciones entre individuos.…”
Section: Comparaciones De Nuestros Resultados Con Estudios En Primateunclassified
“…En relación a los patrones de agrupamiento la hipótesis de depredación postula que la formación de un único grupo (en el que estén incluidos todos los individuos) reduce la probabilidad de depredación aumentando las oportunidades de detectar al depredador antes del ataque (Noë y Bshary 1997;Von Hippel 1998;Capellini et al 2008a, Smith et al 2017. Este patrón de agrupamiento otorga ventajas al grupo ya que son más los individuos que podrían detectar la presencia del depredador y, como todos los individuos están cercanos entre sí, las señales o alarmas que den ante un ataque tiene mayor probabilidad de ser captadas por todos los individuos.…”
Section: Discusión Hipótesis De Depredación (H5)unclassified